2005
DOI: 10.1073/pnas.0501731102
|View full text |Cite
|
Sign up to set email alerts
|

Functional cavitands: Chemical reactivity in structured environments

Abstract: Container-shaped molecules provide structured environments that impart geometric bounds on the motions and conformations of smaller molecular occupants. Moreover, they provide ''solvation'' that is constrained in time and space. When inwardly directed functional groups are present, they can interact chemically with the occupants. Additionally, the potential for reactivity and catalysis is greatly enhanced. Deep cavitands, derived from resorcinarenes, nearly surround smaller molecules and have been one of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
72
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(72 citation statements)
references
References 49 publications
0
72
0
Order By: Relevance
“…[5] The most fascinating feature of top-open resorcin [4]arene cavitands is their ability to adopt two spatially well-defined conformations: an expanded "kite" form and a contracted "vase" form. While various methods have been employed to study the conformational properties of cavitands, [6] the most convenient one is 1 H NMR spectroscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] The most fascinating feature of top-open resorcin [4]arene cavitands is their ability to adopt two spatially well-defined conformations: an expanded "kite" form and a contracted "vase" form. While various methods have been employed to study the conformational properties of cavitands, [6] the most convenient one is 1 H NMR spectroscopy.…”
mentioning
confidence: 99%
“…Since the preparation of the first quinoxaline-bridged resorcin [4]arene cavitand by Cram and co-workers in 1982, [1] numerous derivatives with various structures and functions have been prepared and employed as switches, [2] receptors and sensors, [3] catalysts, [4] and molecular hosts. [5] The most fascinating feature of top-open resorcin [4]arene cavitands is their ability to adopt two spatially well-defined conformations: an expanded "kite" form and a contracted "vase" form.…”
mentioning
confidence: 99%
“…The development in supramolecular chemistry has evolved such that several synthetic systems are now available to also study the reactivity in confined nano-spaces, such as the well-defined cavities of metal-organic frameworks, and (supra)molecular capsules. It has been demonstrated by the pioneering work of Sanders and co-workers 15 , Rebek and co-workers [16][17][18][19] , Fujita and co-workers 20 and Raymond and co-workers 21 that organic reactions that occur in such restricted environments can result in unusual selectivities and rate enhancements. These all are elegant examples in which it has been demonstrated that the activity or selectivity of organic reactions can be controlled by nano-capsules.…”
mentioning
confidence: 99%
“…[6] However, only rare examples describe the endo-complexation of organic guests by calix [4]arenes because of the smallness of their cavity. [7] On the other hand, the larger calix [6]arenes are more difficult to constrain into a given conformation, since these oligomers display a higher flexibility because of the facile "through the annulus" ring inversion of their aromatic units.…”
mentioning
confidence: 99%